Understanding the importance of expanding the definition of interoperability through social network analysis. Issue 2 (18th June 2019) - Enos, James R.; Nilchiani, Roshanak R.
Abstract: Over the past decade, the Department of Defense (DoD) developed an emergent network of systems that operate together on the battlefield to provide value to the DoD. Advances in systems engineering have enabled the DoD to develop better, more integrated, and more complex systems in this time frame. One of the emerging topics in systems engineering is the importance of nonfunctional attributes captured in the ilities of a system. One of these ilities, interoperability, captures the ability of a system to operate with other systems as DoD systems do on the battlefield. This article applies social network analysis tools and methods to understand the effect of expanding the definition of interoperability beyond information flows to include shared resources and physical connections. Social network analysis metrics, such as density and average degree, quantify the effect of expanding interoperability to capture other aspects of interoperability. By capturing these additional aspects of interoperability, the number of connections in the DoD network of systems increases by nearly a factor of four. Thus, if the ility of interoperability narrowly focuses on information flows, then systems engineers could potentially miss a large number of important connections in a network of systems.